2018
DOI: 10.2147/opth.s172109
|View full text |Cite
|
Sign up to set email alerts
|

Assessing reproducibility and the effects of demographic variables on the normal macular layers using the Spectralis SD-OCT

Abstract: PurposeTo quantify and view the possible influence of demographic variables on normal macular layers. Additionally, we wanted to assess the reproducibility using the Spectralis SD-OCT.MethodsA Spectralis SD-OCT machine using a commercially available algorithm was used to scan 242 healthy subjects in an outpatient setting. We examined retinal thicknesses in seven layers: retinal nerve fiber layer (RNFL), ganglion cell layer (GCL), inner plexiform layer (IPL), inner nuclear layer (INL), outer plexiform layer (OP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…The observed age-related TRT decline portrays the retina as an evolving structure, a finding that is well supported in the literature [ 9 , 15 , 18 21 ]. In particular, one review of the literature described the age-related thinning pattern as spatially-dependent, with an unchanged or thickened central retina, and a maximum thickness loss in the parafoveal region [ 9 ].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The observed age-related TRT decline portrays the retina as an evolving structure, a finding that is well supported in the literature [ 9 , 15 , 18 21 ]. In particular, one review of the literature described the age-related thinning pattern as spatially-dependent, with an unchanged or thickened central retina, and a maximum thickness loss in the parafoveal region [ 9 ].…”
Section: Discussionsupporting
confidence: 82%
“…In contrast, we found that the RNFL remained unchanged or even became thicker in some temporal regions. This discrepancy is also present in the literature, with different studies reporting thinning [ 22 , 38 ], no effect [ 18 , 19 ], or thickening [ 20 , 39 ]. These mixed results might be explained by the thinness of the RNFL in relation to the axial resolution, which makes thickness measurements more prone to segmentation errors.…”
Section: Discussionmentioning
confidence: 95%
“…Clinical results have reported that women have thinner retinas than men, without any differences in the foveal pit morphology ( Wagner-Schuman et al, 2011 ), whereas the amplitudes of scotopic and photopic electroretinograms (ERGs) of female subjects have been reported to be on average 29% larger than those of males ( Brûlé et al, 2007 ). Morphological studies have shown gender-related structural differences in thickness of the macular retinal layers by spectral-domain optical coherence tomography (SD-OCT) ( Adhi et al, 2012 ; Hashamani et al, 2018 ). Additionally, the outer nuclear layers and the inner nuclear layer (INL) have been determined to be thicker in men, whereas the nerve fiber layer (NFL) is thicker in women ( Ooto et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested good reproducibility for SPECTRALIS (Heidelberg Engineering Inc, Heidelberg, Germany) OCT for both intraobserver and interobserver studies. These studies have provided general interclass correlated coefficients and have not provided quantifiable data to assist clinicians to detect significant change outside normative variability (2,3).…”
mentioning
confidence: 99%
“…In addition, serial GCL monitoring may identify disease change (2). A normative database of the average thickness of the GCL and/or inner plexiform layer (IPL) and intratest reliability of the mean GCL/IPL thickness for some spectral domain OCT machines exist (3). However, OCT machines use different algorithms to identify the GCL/IPL complex vs the GCL volume, and their findings are not interchangeable.…”
mentioning
confidence: 99%